Local election competition for national party survival: an analysis of Merlimau by-election in Malaysia - Moniruzzaman, Md. (Macrothink Institute, 2016)
Party politics in Malaysia has become tumultuous over the past two decades. As such national and regional level elections as well as by-elections have become equally sensitive for party politics. Of late by-elections have taken a special position as they are considered unseasonal barometer for testing popularity and legitimacy of the incumbent and the opposition competition. The effect of the dramatic 2008 national general elections in Malaysia continued during the subsequent three years through nearly one and a half dozen by-elections throughout the country. Until November 2010, the opposition remained jubilant over its victory in eight out of 11 by-elections maintaining the funfair of the rising opposition unprecedented in Malaysia’s election history. But the tide started to dwindle with the subsequent three wins in Galas, Tenang and Batu Sapi by the ruling coalition turning the trend around. Under this circumstance came the Merlimau by-election in March 2011. Reflecting the reality on the ground, therefore, this by-election became a battleground for party political survival for both the ruling and opposition coalitions. This article discusses the campaign strategies of the competing coalitions, the results of the election, and its implications. The importance of this by-election is that it reflected the intensity of national level electoral sensitivity since the ruling party’s political survival was dependent upon wining this election against a series of by-elections won by the opposition.